2021
DOI: 10.1002/cpe.6342
|View full text |Cite
|
Sign up to set email alerts
|

Artificial neural networks as clinical decision support systems

Abstract: Summary In the last decade, artificial intelligent systems based on neural networks have gradually become primary source for clinical decision support systems (CDSS) and are being used in diverse areas of medical diagnosis, classification, and prediction. An artificial neural network (ANN) consists of a large number of processing units which performs the computation in a parallel and distributed environment. They learn the pattern from the examples provided to it and then generalize based on the concepts they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 131 publications
(131 reference statements)
1
2
0
1
Order By: Relevance
“…According to studies, young, highly educated, and high-income individuals perceive lower levels of service quality [59]. Conversely, elderly, low-educated, and low-income individuals have lower expectations of health services but perceive service quality at a higher level [20,22]. In our study, educational level, marital status, and gender were found to be related to perceived service quality.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…According to studies, young, highly educated, and high-income individuals perceive lower levels of service quality [59]. Conversely, elderly, low-educated, and low-income individuals have lower expectations of health services but perceive service quality at a higher level [20,22]. In our study, educational level, marital status, and gender were found to be related to perceived service quality.…”
Section: Discussionsupporting
confidence: 49%
“…A number of studies conducted within the scope of health services have demonstrated that digital health technologies and artificial intelligence applications are playing an increasingly important role in the delivery of health services [19]. These technologies facilitate the provision of innovative and continuous healthcare services by enhancing the practicality of qualified and accurate patient management, expeditious and high-quality service delivery, and effective communication [20][21][22]. From the perspective of citizens, the utilization of digital health technologies and artificial intelligence applications has the potential to enhance satisfaction with health services.…”
Section: Introductionmentioning
confidence: 99%
“…Dies lässt sich prominent an zwei Beispielen aufzeigen, die teilweise bereits in klinischen Kontexten Anwendung finden: an KI-Systemen zur Bilderkennung und -segmentierung sowie an KI-Entscheidungsunterstützungssystemen (Shafi et al 2021). Die Anwendungsfelder für bilderkennende KI-Systeme sind außerordentlich vielfältig.…”
Section: äRztliche Arbeitserleichterung Auf Sachlicher Ebene Durch De...unclassified
“…In the field of medicine, Artificial Intelligence–driven Decision Support Systems (AI-DSS) are currently receiving much attention. These AI applications based on machine learning or deep learning methods offer great potential to support clinical decision-making ( 2 , 3 ), for example by reducing the workload of medical staff ( 4 ).…”
Section: Introductionmentioning
confidence: 99%